Peranan Pemerintahan Kelurahan dalam Menekan Pernikahan Usia Dini di Kelurahan Tiroang - Hariyani Hariyani (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Abstract This research was a type of descriptive-quantitative and qualitative to provide an overall comprehensive picture of the studied object, which was the role of village government in suppressing early marriage in Tiroang village. The samples used were saturated samples, the entire population was taken as a sample, especially when the population size was relatively small of eighty-five (85) people, and by using instruments such as questionnaires and interviews. The results showed that the role of village government in suppressing early marriage in Tiroang village was instrumental, to name a form of active counseling (63,53%), and active guidance (52,94%). As for the highly influencing factors were education (50,59%), the community (50,59%), and the cultural factor (60%).